PELATIHAN MENANAM HIDROPONIK DALAM UPAYA KETAHANAN PANGAN DI DESA NGEJENG BOJONEGORO - Ari Kuntardina; Nurrahma Luckysyah; Widya Septiani Shofyanna; Maulida Rohmatul Laeliya; Neli Agustina; Delia Kholifatul Mala; Rima Fatmawati; Rizal Aryanto; Anita Firdous Alifia (Universitas YPPI Rembang, 2021)
The impact of the Covid-19 pandemic affected most of the people of Ngrejeng village, Purwosari District, Bojonegoro Regency. Some people have been temporarily dismissed and some have even lost their jobs. The aim of this program is to empower the community by providing training in farming with a hydroponic system. The concept of